Implementasi Protokol RF24Mesh dalam Wireless Sensor Network pada Lahan Pertanian - Alldo Raafi'ilman; Adhitya Bhawiyuga; Reza Andria Siregar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Monitoring technology could bring benefit to the agricultural sector. By monitoring the condition of the surrounding environment of the crop, the farmers could get the data regarding the condition of the crops and able to take action to maintain the condition of the crops so the harvest will yield the best result. This monitoring technology could be made possible by building a wireless sensor network. Wireless sensor network is a network that consist of numerous sensor node that connected via wireless media. To cover the whole crop field a flexible and easily configurable media is needed. RF24Mesh protocol is a flexible protocol thanks to the mesh based network it operates on and have an automatic configuration. The network that has been built and implemented in this study has proved to be able to fulfill the requirements for agricultural use which is collecting data from sensors. The test results reveal that 0-10% packet loss occured in 100 continuous transmission in different scenarios with various end-to-end delay ranging from 0,74 seconds to 0,94 seconds.